LEGAL COUNSELING ON REVISION OF THE MANPOWER LAW AND THE RIGHTS AND OBLIGATIONS OF EMPLOYEES TO INCREASE LITERACY AWARENESS AT PT LONGTHAI RECREATION BATAM - Winsherly Tan; Cynthia Putri Guswandi (ConCEPt - Conference on Community Engagement Project, 2022)
The law changes following developments that occur in the community, this is done so that the applicable law can prevent problems from arising and overcome problems that occur in the community. As with Law no. 13 of 2003 concerning Manpower which was revised through the Omnibus Law on Job Creation (Law No. 11 of 2020). The Manpower Act is a regulation that regulates all matters concerning employers and employees. The Employment Creation Law changes, adds and deletes several articles contained in the Manpower Act which are deemed necessary for renewal. However, the enactment of the Job Creation Law has sparked public controversy because it is considered inefficient and detrimental to employees. The method used in this research is a lecture which is then processed into a qualitative form. Data was collected by means of observation and interviews through questionnaires. This legal counseling aims to inform the Job Creation Act and the rights and obligations of employees and so that the public, especially employees, understand more about the applicable laws regarding emploment.